The association between infections and chemotherapy interruptions among cancer patients: Prospective cohort study. Issue 3 (March 2015) - Taha, Ahmed; Vinograd, Inbal; Sakhnini, Ali; Eliakim-Raz, Noa; Farbman, Laura; Baslo, Rina; Stemmer, Salomon M.; Gafter-Gvili, Anat; Leibovici, Leonard; Paul, Mical
Summary: Objectives: Adherence to scheduled chemotherapy is important for optimal outcomes of cancer patients. We examined causes for delay or cancellation of planned chemotherapy, focusing on mild respiratory infections during the winter. Methods: Prospective cohort study. We included all adults with solid or hematologic cancer receiving active chemotherapy treatment during the winter of 2010–2011 in a cancer center. We compared baseline characteristics and outcomes between patients with and without chemotherapy delays, cancellations, or dose-reductions ("chemotherapy delay"). Results: We included 547 patients receiving chemotherapy during the winter of 2011. Of these, 213 (38.9%) patients experienced 306 episodes of chemotherapy delays. The main documented reasons for the chemotherapy delay were neutropenia (84/306, 27.4%), fever or infection (73/306, 23.9%) and thrombocytopenia (26/306, 8.5%). Independent risk factors for chemotherapy delays were upper respiratory infections (OR 1.87, 95% CI 1.27–2.76), lymphopenia, prior hospitalization, peripheral vascular disease and colon cancer relative to hematologic cancer. In the adjusted analysis focusing on chemotherapy delays due to infection alone, upper respiratory infections (OR 5.25, 95% I 2.81–9.84) and age were significant independent risk factors. Discussion: Mild respiratory infections were associated with chemotherapy delays. Our results should encourage modalities to prevent influenza and other upper respiratory infections among cancer patients.